Effect of Content Marketing, Customer Engagement, and Brand Trust on Brand Loyalty (Survey on users of the “Bareksa” Digital Investment Platform) - Rifaldi, M. Diky; Gaffar, Vanessa (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of content marketing, customer engagement, and brand trust on brand loyalty among users of the digital investment platform